2015
DOI: 10.1002/ppul.23304
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis, monitoring, and treatment of primary ciliary dyskinesia: PCD foundation consensus recommendations based on state of the art review

Abstract: SummaryPrimary ciliary dyskinesia (PCD) is a genetically heterogeneous, rare lung disease resulting in chronic oto‐sino‐pulmonary disease in both children and adults. Many physicians incorrectly diagnose PCD or eliminate PCD from their differential diagnosis due to inexperience with diagnostic testing methods. Thus far, all therapies used for PCD are unproven through large clinical trials. This review article outlines consensus recommendations from PCD physicians in North America who have been engaged in a PCD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
438
3
68

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 343 publications
(538 citation statements)
references
References 161 publications
7
438
3
68
Order By: Relevance
“…There is no clear consensus on the best treatment option for chronic rhinosinusitis in PCD [12,48]. Sinus irrigation is a safe, cheap and normally well tolerated treatment option, but studies are needed to assess its effectiveness in PCD.…”
Section: Upper Airway Managementmentioning
confidence: 99%
See 4 more Smart Citations
“…There is no clear consensus on the best treatment option for chronic rhinosinusitis in PCD [12,48]. Sinus irrigation is a safe, cheap and normally well tolerated treatment option, but studies are needed to assess its effectiveness in PCD.…”
Section: Upper Airway Managementmentioning
confidence: 99%
“…A recent study found age-dependent changes in bacterial pathogens in the lower respiratory tract, with Haemophilus influenzae and Moraxella catarrhalis being more frequent in children and P. aeruginosa in teenagers and adults [61]. Antibiotic prophylaxis should be considered if repeated courses of antibiotics are required [12,48], but prospective studies on the use of prophylaxis [62] and on different prophylaxis regimes are needed.…”
Section: Lower Airway Managementmentioning
confidence: 99%
See 3 more Smart Citations